Human RECQ1 promotes restart of replication forks reversed by DNA topoisomerase I inhibition - Berti, Matteo; Ray Chaudhuri, Arnab; Thangavel, Saravanabhavan; Gomathinayagam, Shivasankari; Kenig, Sasa; Vujanovic, Marko; Odreman, Federico; Glatter, Timo; Graziano, Simona; Mendoza-Maldonado, Ramiro; Marino, Francesca; Lucic, Bojana; et al. (Nature structural & molecular biology, 2013)
The cytotoxic effects of topoisomerase I inhibitors such as camptothecin can be modulated by replication fork reversal, in a process that requires Poly(ADP-ribose) polymerase (PARP) activity. Here human RECQ1 helicase is shown to restore such regressed replication forks, whereas PARP1 activity restrains this RECQ1 function. Topoisomerase I (TOP1) inhibitors are an important class of anticancer drugs. The cytotoxicity of TOP1 inhibitors can be modulated by replication fork reversal through a process that requires poly(ADP-ribose) polymerase (PARP) activity. Whether regressed forks can efficiently restart and what factors are required to restart fork progression after fork reversal are still unknown. We have combined biochemical and EM approaches with single-molecule DNA fiber analysis to identify a key role for human RECQ1 helicase in replication fork restart after TOP1 inhibition that is not shared by other human RecQ proteins. We show that the poly(ADP-ribosyl)ation activity of PARP1 stabilizes forks in the regressed state by limiting their restart by RECQ1. These studies provide new mechanistic insights into the roles of RECQ1 and PARP in DNA replication and offer molecular perspectives to potentiate chemotherapeutic regimens based on TOP1 inhibition.